Case Study Analysis of Conflict Dynamics in Ukraine, 2022–2027 - Maria Bordas; Janos Tomolya (European Scientific Journal, ESJ, 2026)
The Russia–Ukraine conflict, initiated during the 2014 regional territorial onset and systematically altered by the 2022 full-scale military invasion, has undergone a profound structural transformation in its fifth year of high-intensity warfare. This systemic realignment has severely compromised post-Cold War multilateral frameworks, shifting the diplomatic paradigm toward highly fragmented and transactional negotiation structures. This study aims to evaluate the contemporary structural transformation of the geopolitical landscape, specifically analysing how shifting international mediation dynamics and external diplomatic variables influence potential conflict resolution pathways. Utilizing a qualitative, comparative scenario-analysis methodology grounded in neorealist international relations theory, this paper operationalizes and assesses the strategic trajectories of the conflict.The analytical framework operationalizes China’s policy of "constructive ambiguity" as a distinct category of macroeconomic and technological alignment, and evaluates the foreign policy trajectories of the United States administration through a transactional structural framework. The analysis reveals that the core strategic "red lines" of the belligerents remain politically and mathematically mutually exclusive, as demonstrated by contemporary empirical data from the June 2026 diplomatic initiatives. The findings indicate that the "Korean Peninsula model", operationalized as a de facto territorial partition under an unsigned armistice, and "armed neutrality", conceptualized as a non-aligned, heavily fortified state model sustained by Western bilateral defence treaties, constitute the only structurally plausible mid-term trajectories. The scholarly implications of this study suggest that a durable resolution cannot be achieved through ad hoc diplomatic expedients or superficial ceasefire lines. Long-term regional stability structurally necessitates a fundamental stabilization of the multilateral security architecture capable of enforcing mutual compromises and binding institutional guarantees.